Python Deep Learning Projects : 9 projects demystifying neural network and deep learning models for building intelligent systems /: 9 projects demystifying neural network and deep learning models for building intelligent systems. (2018) - Lamons, Matthew; Kumar, Rahul; Nagaraja, Abhishek
No abstract available